Analisis perbandingan antara rencana strategis Baitul Maal wat Tamwil di Indonesia berdasarkan fokus layanan - Janan, Akhmad Syifaul; Mahasin, Ahmad Ulul; Arfyansya, Mohammad Arya (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to analyze the comparison between Baitul Maal wat Tamwil’s strategic plans in Indonesia based on their service focus. The analysis tool used is SWOT (Strength, Weakness, Opportunity and Threat) for BMT Arta Bina, BMT MMU Sidogiri and also BMT BUS Lasem. This research uses qualitative methods by reviewing literature from previous research through collecting primary and secondary data. The research results show that BMT Arta Bina focuses more on small communities, BMT MMU refers more to the activities and management of BMT MMU members while BMT BUS Lasem focuses more on fishermen around the north coast of Java. All BMTs have good performance, especially in product and service variables with sharia financial principles.